Scientific Knowledge about Poultry Broiler Farming in Barabanki District of Uttar Pradesh - Jitendra Pratap , M. P. Sagar , Mahesh Chander , N. K. Khyalia and A. K. Chaturvedani, (Indian Journal of Extension Education, 2017)
The present investigation was carried out to study the scientific knowledge about broiler farming among poultry farmersin Barabanki district of Uttar Pradesh. Fifteen poultry farmers were selected randomly from each block, making a totalsample size of 75. To measure the knowledge level of respondents with regard to scientific broiler farming practices, astructured pretested interview schedule was developed consisting of 72 objective type questions related to seven majorareas like housing, brooding, feeding, bio-security and disease control, finance, marketing and poultry insurance. Everycorrect answer was given score one and incorrect score zero. The total knowledge score of the respondent was obtained byadding scores of all the correct answers out of 72 questions. The lowest score that a respondent could obtain was zero andthe highest was 72. On the basis of overall knowledge score, the respondents were classified into three categories as low,medium and high on the basis of equal interval between maximum and minimum knowledge score. The study revealedthat all the small poultry farmers had medium level of scientific knowledge about feed and feeding management practices,housing management practices and brooding management practices (in overwhelming majority), while all the largepoultry farmers had high level of scientific knowledge about housing management practices, breed selection andidentification of quality chicks, feed and feeding management practices and poultry insurance. All the medium poultryfarmers were found to have medium level of scientific knowledge about bio-security and disease control practices,finance, marketing and poultry insurance, while overwhelming majority of them (93.75%) were having high level ofknowledge about feed and feeding management practices. Majority of medium poultry farmers were found to possessmedium level of knowledge about brooding management, breed selection and identification of quality chicks while, highlevel of knowledge about housing management practices. Majority of them had high level of knowledge about feed andfeeding management practices. Further, comparison of knowledge level about scientific broiler farming among thedifferent categories of poultry farmers using one way ANOVAwas also done and the results show that small, medium andlarge poultry farmers were found to differ significantly at 1per cent level of significance (p